Kelayakan Finansial dan Ekonomi Perkebunan Tebu Rakyat pada Proyek Kemitraan Petani dan Pabrik Gula di Kabupaten Sragen - Agus Santosa; Budi Widayanto (Jurnal Dinamika Sosial Ekonomi, 2001)
The extent of demand share of care commodity should become an appropriate lesson for the domestic cane business people, mainly farmer and sugar mill. The issue, how is the feasible of the people cane farming financially and economically and what the farmer do to recover the. The purposes of this paper are to analyze the financial and economic feasibility and to determine the sensitivity level of farming from various price changes. The calculation result indicates that the project of cane farming is either financially or economically feasible. The reason are: NPV has positive value DPP is achieved after the second yearth of the project, but the farming is so sensitive to the price change of cane and production means that it needs on going effort to maintenance the feasibility of the farming.Keywords: care commodity, financial and economic feasibility, partnership